Naturally Occurring Cathinone From Khat, Synthetic Cathinones and Cytochrome P450 - Sharoen Yu Ming, Lim; Mustafa, Ahmed Alshagg; Chin Eng, Ong; Yan, Pan (Springer Nature Switzerland AG, 2022)
Cathinone is the main euphorigenic compound found in khat plant. It is controversial to claim that khat use is a form of addiction or abuse as it is social custom and pride for khat-belt countries. Khat and cathinone are often co-administered with medications leading to possible khat-drug and/or cathinone-drug interactions. Despite the belief that khat is effective in relieving tuberculosis and Parkinson illnesses, khat has negatively impacted the socioeconomic and educational attainment of children, while cathinone abuse is inclined to suicide and fatalities. Continuous modifications are in producing new synthetic cathinones for market demand and to circumvent the legislations, making it a continuous effort to elucidate the mechanism of actions of new cathinones. This chapter rules out prevalence of khat/cathinone abuse, the underlying mechanism of CYPs and synthetic cathinones, current legislation, and the discovery of high affinity anticathinone vaccines giving hope for the future to curb cathinone addiction.